Photoinitiated cationic polymerization using allylsulfonium salts. Substituent effect on the initiator activity - Bayramoglu, Fatma; Onen, Aysen; Yagci, Yusuf (Walter de Gruyter GmbH, 2001)
Abstract Allylthiophenium salts with various substituents at the allylic moiety were synthesized, characterized and shown to be efficient coinitiators in radicallly promoted cationic photopolymerization of cyclohexene oxide. The relative efficiencies of these salts in combination with benzoin and benzophenone as free radical sources in the photopolymerizations are compared. Both additionfragmentation and electron transfer mechanisms are proposed and their relative merits discussed.